A Simulation‐based Approach to Measuring Team Situational Awareness in Emergency Medicine: A Multicenter, Observational Study. (12th October 2017) - Rosenman, Elizabeth D.; Dixon, Aurora J.; Webb, Jessica M.; Brolliar, Sarah; Golden, Simon J.; Jones, Kerin A.; Shah, Sachita; Grand, James A.; Kozlowski, Steve W. J.; Chao, Georgia T.; Fernandez, Rosemarie
Abstract: Objectives: Team situational awareness (TSA) is critical for effective teamwork and supports dynamic decision making in unpredictable, time‐pressured situations. Simulation provides a platform for developing and assessing TSA, but these efforts are limited by suboptimal measurement approaches. The objective of this study was to develop and evaluate a novel approach to TSA measurement in interprofessional emergency medicine (EM) teams. Methods: We performed a multicenter, prospective, simulation‐based observational study to evaluate an approach to TSA measurement. Interprofessional emergency medical teams, consisting of EM resident physicians, nurses, and medical students, were recruited from the University of Washington (Seattle, WA) and Wayne State University (Detroit, MI). Each team completed a simulated emergency resuscitation scenario. Immediately following the simulation, team members completed a TSA measure, a team perception of shared understanding measure, and a team leader effectiveness measure. Subject matter expert reviews and pilot testing of the TSA measure provided evidence of content and response process validity. Simulations were recorded and independently coded for team performance using a previously validated measure. The relationships between the TSA measure and other variables (team clinical performance, team perception of shared understanding, team leader effectiveness, and team experience) were explored. The TSA agreement metric was indexed by averaging the pairwise agreement for each dyad on a team and then averaging across dyads to yield agreement at the team level. For the team perception of shared understanding and team leadership effectiveness measures, individual team member scores were aggregated within a team to create a single team score. We computed descriptive statistics for all outcomes. We calculated Pearson's product‐moment correlations to determine bivariate correlations between outcome variables with two‐tailed significance testing (p < 0.05). Results: A total of 123 participants were recruited and formed three‐person teams ( n = 41 teams). All teams completed the assessment scenario and postsimulation measures. TSA agreement ranged from 0.19 to 0.9 and had a mean (±SD) of 0.61 (±0.17). TSA correlated with team clinical performance (p < 0.05) but did not correlate with team perception of shared understanding, team leader effectiveness, or team experience. Conclusions: Team situational awareness supports adaptive teams and is critical for high reliability organizations such as healthcare systems. Simulation can provide a platform for research aimed at understanding and measuring TSA. This study provides a feasible method for simulation‐based assessment of TSA in interdisciplinary teams that addresses prior measure limitations and is appropriate for use in highly dynamic, uncertain situations commonly encountered in emergency department systems. Future research is needed to understand the development of and interactions between individual‐, team‐, and system (distributed)‐level cognitive processes.